Digital economy and financial inclusion in reviving the national economy: A Management Strategy - Sudiantini, Dian; Rizky, Putri Puspita; Hazarika, Anurag (CV. Bimbingan Belajar Assyfa, 2023)
This research aims to analyze the role of the digital economy and financial inclusion in accelerating Indonesia's national economic recovery. With increased funding allocations for economic recovery, the Indonesian government is facing fiscal challenges, including diverting budget from the health sector. This research uses a qualitative research design with a literature review method to evaluate national economic recovery strategies. The focus of this research is on start-up companies and individuals with digital funding accounts. The research results show that a digital economic ecosystem supported by better financial inclusion can accelerate the process of national economic recovery. These findings emphasize the importance of developing integrated management strategies to support small and medium enterprises and expand access to digital financial services.